Bismuth exposure affects morpho-physiological performances and the ionomic profile in garden cress (Lepidium sativum L.) plants - Pietrini, Fabrizio; Passatore, Laura; Carloni, Serena; Massimi, Lorenzo; Astolfi, Maria Luisa; Giusto, Chiara; Zacchini, Massimo (Frontiers in Environmental Science, 2023)
Environmental pollution caused by heavy metals has long been considered a relevant threat to ecosystem survival and human health. The use of safer substitutes for the most toxic heavy metals in many industrial applications is discussed as a potential way to face this issue. In this regard, Bi has been proposed for replacing Pb in several production processes. However, few literature is reported on the effects of Bi on living organisms, particularly on plants. In this study, garden cress (Lepidium sativum L.) plants were exposed to different concentrations of Bi nitrate added to soil in growth chambers for 21 days. Results evidenced the toxic effect of Bi on the shoot growth, regardless of the Bi nitrate concentration in the soil, paralleled by a similar reduction in the chlorophyll and carotenoid content, a decrease in the Nitrogen Balance Index (NBI) values, and an impairment of the photosynthetic machinery evaluated by the chlorophyll fluorescence image analysis. The presence of Bi in the soil was shown to affect element accumulation in roots and translocation to shoots, with micronutrient content particularly reduced in the leaves of Bi-treated plants. A dose-dependent plant accumulation of Bi to metal concentration in the soil was observed, even if very low metal bioconcentration ability was highlighted. The reduced Bi translocation from roots to shoots in plants exposed to increasing Bi concentrations in the soil is discussed as a possible defense mechanism likely associated with the observed increase of the anthocyan and flavonol contents and the activation of photoprotection mechanisms preventing higher damages to the photosynthetic apparatus.